Roppo dan Sandeq: Budaya Maritim dan Identitas Masyarakat Adat Suku Mandar di Sulawesi Barat - Wulandah, Safirah; Wilodati, Wilodati (Universitas Negeri Medan, 2025)
Indonesia is the largest maritime country in the world, one of its regions is West Sulawesi. In this region, the Mandar tribe lives, the majority of whose people work as sailors. The culture or local wisdom of the Mandar tribe, namely roppo and sandeq, is a maritime culture and identity of the Mandar tribe. The purpose of this research is to explain the local wisdom of roppo and sandeq as a maritime culture and identity of the Mandar tribe of West Sulawesi. This research is a qualitative research with a case study method that comes from various sources of books, articles and so on about roppo and sandeq in the Mandar tribe of West Sulawesi. The results of this study are (1) roppo and sandeq are the maritime culture of the Mandar tribe because the Mandar region is a maritime region, (2) roppo and sandeq become the identity of the Mandar tribe's indigenous people because the characteristics of the Mandar people are dubbed as